Resilient Parents… Resilient Communities: A Pilot Study Trialing the Bounce Back and Thrive! Resilience-Training Program With Military Families - Mikolas, Cynthia; Pike, Ashley; Jones, Chelsea; Smith-MacDonald, Lorraine; Lee, Melina; Winfield, Hope; Griffiths, Jennifer; Perry, Ryan; Olson, David M.; Heber, Alexandra; Olson, Joanne; Sevigny, Phillip R.; et al. (Frontiers in Psychology, 2021)
Introduction: The resilience of Canadian military families (CMFs) - the main support of the Canadian Armed Forces service members (SMs) - is imperative. The Canadian Armed Forces aims to ensure that SMs and their families are resilient and SMs ready to respond when called upon for combat, peacekeeping or pandemic/disaster-response. Family concerns, however, can realistically distract SMs from the mission, potentially compromising themselves, their unit and the mission. Resilience-training programs such as Bounce Back and Thrive! (BBT) can help families manage the realities of military life. Objective: This pilot study aimed to evaluate suitability of BBT implementation by Military Family Resource Centers (MFRCs), including whether BBT: (1) fosters resilience-building among parents, (2) facilitates CMF resilience-building, (3) can be contextualized for CMFs, and (4) supports MFRCs in cultivating a culture of resilience. Methods: An exploratory qualitative design was used. BBT was offered to parents face-to-face. Participants completed focus groups after the first 6 sessions, final 4 sessions, and one-year post-intervention. Data was thematically analyzed. Results: Nine military parents participated. Four major themes resulted: (1) military parent resilience-building, (2) CMF resilience-building, (3) BBT program feedback and contextualization, and (4) MFRCs as community resilience hubs. Discussion: BBT enabled parents to gain a new perspective on resilience, engage in dialogue and intentionally role model resilience skills. Military-specific BBT contextualization and online-delivery formats would increase suitability and access for CMFs. Access to resilience programs delivered through MFRCs would support CMFs. Further research is warranted.